An Analysis of Maxim Violations in Stan and Ollie Movie - Sri Dwi Hardianti; Dohra Fitrisia; Chairina Nasir (Research in English and Education Journal, 2023)
This research presents the violation of maxims by Stan, Ollie, Lucille, Ida, Mr. Hal, Mr. Delfont in Stan Ollie movie. The objective of this qualitative study is to find and analyze the types of maxims that are violated in the conversation Stan Ollie movie and the reasons for the speakers to violate Grice’s maxim. It employs the cooperative principal theory by Grice (1975) and Dornerus (2005) to guide the researcher in analyzing the type of maxims that are violated in Stan Ollie movie. The theory from Christoffersen (2005) in Tupan Natalia (2008) is also used to analyze the reasons behind the violations. The findings of this research shows that the highest maxim violation is maxim of quality (60.4%), followed by maxim of manner (25%), and then maxim of relevance (10.4%), and the least is maxim of quantity (4.2%). Furthermore, the reasons behind the utterance are hiding the truth (14), saving face happened (1), feeling jealous about something (8), satisfying the hearer happened (1), cheering the hearer (13), avoiding to hurt the hearer happened (2), building one’s belief happened (3), and convincing the hearer happened (3). Due to the result of this research, it is recommended that people should employ cooperative principle while conversing in order to avoid violating the maxims and for information to be conveyed appropriately.